Suitable Stages for Isolation and Culture PGCs from Chicken Embryos - Li, B.C.; Chen, G.H.; Qin, J.; Wu, X.S.; Wu, S.L.; Cai, Z.T. (International Journal of Poultry Science, 2005)
The aim of this study was to evaluate the efficiency of isolation and culture of PGCs from various tissues of chicken embryos at specific developmental stages including: the circulating blood of stage 14 embryos (hatched for 48-52hrs), the genital ridge of stage 19 embryos (hatched for 68-72hrs) and the gonad of stage 28 embryos (hatched for 128-132hrs). Ficoll density-gradient centrifugation is a standard method for the purification of PGCs from fetal blood. The genital ridge and gonadal tissue contain more PGCs in total but must first be digested with trypsin-EDTA to give a single cell suspension containing a mixture of PGCs and other contaminating cell types. In these experiments, we cultured PGCs from the genital ridge and from gonadal tissue before and after Ficoll density-gradient purification. In all cases, PGCs were subsequently cultured in TCM-199 medium supplemented with 10% fetal calf serum. The results demonstrated that trypsin-EDTA alone of the genital ridge of stage 19 embryos yielded a total of2.7 x 104 per embryo of which 89.5% were viable. After Ficoll density-gradient purification of these cells the yield was 1.8 x 104 of which 87.5% were viable. Processing of the gonadal tissue of stage 28 embryos yielded a total of 3.1 x 104 PGCs per embryo of which 90.0% were viable. It was clear that the PGC yield with trypsin-EDTA alone was higher (P< 0.01) than the yield of the full procedure which included the Ficoll density-gradient purification step. The results of PGC culture from the three developmental stages indicated that the survival time was longest (80-88 hours) for PGCs obtained from stage 19 embryos. At this stage, a large number of PGCs had accumulated in the genital ridge which facilitated the isolation procedure. These results suggest that the highest yield of PGCs per embryo can be achieved by trypsin-EDTA treatment of genital ridge tissue from stage 19 chicken embryos.